The value of carcinoembryonic antigen stage in staging, prognosis, and management of colorectal cancer: results from two cohort studies - Xie, Hailun; Wei, Lishuang; Liu, Mingxiang; Liang, Yanren; Wang, Qiwen; Tang, Shuangyi; Gan, Jialiang (Frontiers in Oncology, 2023)
Background: Combining the carcinoembryonic antigen (CEA) level (C stage) with TNM staging can provide a more comprehensive prognostic assessment of colorectal cancer (CRC). However, the clinical value of incorporating CEA status into the TNM staging system needs to be evaluated.We used the SEER database (N = 49,350) and a retrospective cohort from China (N = 49,350). A normal CEA level was staged as C0 and an elevated CEA level was staged as C1. Restricted cubic spline analysis was used to examine the doseresponse relationship between the CEA level and survival. The Kaplan-Meier method with the log-rank test was used to plot survival curves. Multivariable Cox proportional hazards regression models with forward stepwise variable selection were used to estimate the hazard ratios and 95% confidence intervals.Results: Patients with C1 were more likely to have advanced disease than those with C0. CEA on a continuous scale was positively associated with mortality risk. Compared with patients with C0 stage, those with C1 stage had significantly lower survival rates.In the SEER dataset, C1 was independently associated with poor prognosis in patients with CRC, with an approximately 70% increased risk of mortality. Patients with C1 stage had significantly lower survival than those with C0 stage at all clinical stages.Incorporating the C stage into the TNM staging refined the prediction of prognosis of patients with CRC, with a gradual decline in prognosis from stage I C0 to stage IV C1.A similar pattern was observed in the present retrospective cohort study. At each lymph node stage, patients with C1 had significantly lower 5-year survival rates than patients with C0. Compared with lymph node positivity, CEA positivity may have a stronger correlation with a worse prognosis.Our findings not only validated the independent prognostic significance of CEA in CRC but also demonstrated its enhanced prognostic value when combined with TNM staging. Our study provides evidence supporting the inclusion of C stage in the TNM staging system.